HUBUNGAN KEBIASAAN SARAPAN, KECUKUPAN ENERGI SARAPAN, DAN EMOTIONAL EATING DENGAN STATUS GIZI LEBIH DI SMA BUDHI WARMAN 2 JAKARTA - Zahroh 'Aliyatul 'Izzah (2023)
Background: Based on RISKESDAS 2018, the prevalence of adolescent age 16 - 18 years old that overweight in DKI Jakarta is at 21,1%. Adolescent with overweight have a higher chance to degenerative disease. Overweight on adolescent can be caused by a over intake in dieary habit, physical activity, and stress. Objective: To determined the relationship between breakfast habit, adequate energy intake on breakfast, and emotional eating with overweight in SMA Budhi Warman 2 Jakarta. Methods: This study used cross-sectional design with quatitative approach. The sampling technic using a purposive sampling with 136 respondents from grade X and XI. Data analysis for this study is using Chi-Square test. Result: Based on the anylisis results, there are no relationship between breakfast habit, adequate energy intake on breakfast, and emotional eating with overweight in SMA Budhi Warman 2 Jakarta (p value = 0,194; 0,400; 0,842). Conclusion: There are no relationship between breakfast habit, adequate energy intake on breakfast, and emotional eating with overweight in SMA Budhi Warman 2 Jakarta. Although, it can be seen that student whose had a breakfast tend to not overweight and student whose skipping breakfast tend to overweight.